Basic educational competences of stomatology professors: their improvement - Clotilde de la Caridad Mora Pérez; Maria Elena Cobas Rodriguez; Jorge Rodríguez López; Pedro Alvarez Rodríguez; Maricela Seijo Machado; Sahily Espino Otero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Stomatology professors should master the appropriate educational competences to make the students learn and build their own learning according to contemporary pedagogical trends in Medical Education. Objective: To identify the existing deficiencies in professionals´ educational competences. Method: Quantitative-qualitative development research in Stomatology career from 2006 to December 2007. This research included 25 professors and the studied variables were: graduation year, experience, educational categorization, pedagogical training and educational competences. Different instruments were applied to professors, students, and directors and a team of experts was formed to work as a nominal group. From the collected data an enabling system of actions was designed. Date was processed using SPSS software version 15.0 for Windows. Results: Deficiencies in the development of educational competences were found, negatively influencing educational quality, mainly in the understanding of teaching objectives, and in teaching methods leading to an inappropriate pedagogical investigation. Conclusions: Deficiencies in the development of educational competences have an impact on the quality of the future professional. This study is a viable alternative to improve Stomatology professionals in our National Health System.